A new approach for disruption management in airline operations control - António Castro (2014)
As a sequel of a recent Ph.D. thesis at the University of Porto and LIACC research lab, a new book appeared at Springer, Series: Studies inComputational Intelligence, Vol. 562, 2014, XII, 242 p., entitledA New Approach for Disruption Management in Airline Operations Controlby Antonio J. M. Castro, Ana Paula Rocha, and Eugénio Oliveira.The relevance of this book is mainly to show how the multi-agent system paradigm can be used to solve a very relevant real life real size problem.The book introduces a new concept for disruption management in current Airline Operations Control Centers, taking into account their organization, tools, problems, methods and costs.Most of the research efforts dealing with airline scheduling have been done through off-line plan optimization methods. However, nowadays, with the increasingly complex and huge traffic at air ports, the real challenge is how to react to unexpected events that may cause plan disruptions,leading to flight delays.Moreover these disruptive events usually affect at least three different dimensions of the situation: the aircraft assigned to the flight, the crewassignment and, often forgotten, the passengers' journey and satisfaction.